Serious board games: modding existing games for collaborative ideation processes - Micael Sousa (Serious Games Society, 2021)
Modern board games are booming, exploring new design elements, and providing dynamics that can support unique experiences. Serious game approaches can benefit from these insights and novelty. With the appropriate adaptation, modern board games may become flexible and cheaper ways to use and prototype serious games. Exploring these games and player engagement can support digital game design. Digital game designers may learn from modern board games to playtest player engagement and build prototypes for their serious games. This paper describes an experience with several adapted modern board games aiming to create a "Light Collaborative Ideation Process", supported by the "Engagement Design" model and "The big five personality traits". The game session objectives concerned fostering collaboration and ideation among participants in an informal meeting. The session successfully supported the potential of using modern board games, although showing the limitations and future developments required to benefit from the modding approach.